2013
DOI: 10.3109/09638288.2013.837104
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial difficulties in alcohol dependence: a systematic review of activity limitations and participation restrictions

Abstract: Alcohol dependence profoundly affects the family and social network of the afflicted person. The most frequent difficulties in activities and participation have to do with interpersonal interactions, economic and work life, dealing with aggression and legal problems. Problems with high-risk behaviours and in seeking appropriate treatment are also common. Treatment targeted at reduction or cessation of alcohol use is effective in reducing these psychosocial difficulties. The ICF offers a structure for systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 130 publications
0
40
0
2
Order By: Relevance
“…Social impairment is one of the most detrimental features of alcohol use disorder (AUD) (1). The negative effect of chronic alcohol use on social skills is one of the potential important contributors to poor social functioning in AUD.…”
Section: Introductionmentioning
confidence: 99%
“…Social impairment is one of the most detrimental features of alcohol use disorder (AUD) (1). The negative effect of chronic alcohol use on social skills is one of the potential important contributors to poor social functioning in AUD.…”
Section: Introductionmentioning
confidence: 99%
“…First, variables that referred to information about functioning and disability were grouped by similarity of contents into overarching categories according to Popay's guidelines about how to analyse narrative reviews (Popay et al, 2006). Second, to grade the level of evidence we used an adaptation of van Tulder's grading used in several studies (van Tulder et al, 2003;Nieuwenhuijsen et al, 2008;Cabello et al, 2012;Levola et al, 2014): evidence was assessed as 'strong' if there were at least two good studies reporting the same results, 'limited' if there was only one good and some acceptable studies reporting the same result, and 'controversial' in the case of studies reporting contrasting results. In cases where the results were reported in only one study, or if no good study reported the results, the evidence was assessed as 'inconsistent'.…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%
“…Level of evidence: **strong evidence; *limited evidence(van Tulder et al, 2003;Nieuwenhuijsen et al, 2008;Cabello et al, 2012;Levola et al, 2014).…”
mentioning
confidence: 99%
“…El alcoholismo se considera uno de los principales problemas de salud pública en el mundo, por su impacto sobre las áreas social, cultural, jurídica y económica (Levola et al, 2014). Las tasas de enfermedad mental en la población joven se ven incrementadas en aproximadamente el 15%, en parte, por la tendencia al abuso de alcohol en edades cada vez más tempranas (American Psychiatric Association [APA], 2013; King y Chassin, 2004;Organización Panamericana de la Salud, 2008).…”
Section: Introductionunclassified